Persistent low-density infection in areas at risk of malaria reintroduction in Malaysia - Adela Ida Jiram; Shamilah Hisam; Mohd Hafizi Abdul Hamid; Jenarun Jelip; Rahmah Noordin; Kamarul Imran Musa; Nurhainis Ogu Salim; Noor Azian Md Yusuf; Nur Fariha Amir; Aliaa Rasyidina; Nor Parina Ismail; Dg Izyan Hazwani Aziz; et al. (PLoS ONE, 2025)
Malaysia successfully achieved zero indigenous human malaria cases since 2018. However, challenges persist from Plasmodium knowlesi (zoonotic malaria) and low-density infections, posing reintroduction risks in previously malaria-free areas. Addressing these hidden infections is critical for sustaining Malaysia’s elimination gains. This study investigated the persistence of low-density malaria transmission in high-risk localities declared malaria-free for at least three consecutive years. A community-based cross-sectional survey was conducted from June to October 2020 in 23 high-receptivity localities across Sabah, Perak, Kelantan, and Johor. Blood samples from asymptomatic residents were screened via conventional microscopy and nested PCR (nPCR) targeting the Plasmodium 18S rRNA gene, with positive nPCR products species-determined. Sociodemographic and geospatial data were analyzed for associations with infection status. Of 3,322 asymptomatic individuals, no infections were detected by microscopy, whereas nPCR revealed a low-density malaria prevalence of 1.86% (62/3,322). Infections comprised P. malariae (40.3%), P. vivax (29.0%), P. knowlesi (24.2%), P. falciparum (1.6%), P. cynomolgi (1.6%), and mixed P. vivax/P. knowlesi (3.2%). All PCR-positive cases originated from Sabah and an Orang Asli settlement in Perak. Adults (≥17 years) constituted the majority (~68%), with no significant difference in prevalence by gender or previous malaria history (p > 0.05). Asymptomatic low-density malaria infections persist in purportedly malaria-free communities, remaining undetectable by routine microscopy. These hidden parasite reservoirs pose a risk for malaria reintroduction, especially in receptive areas. Malaria surveillance programs must thus incorporate highly sensitive diagnostic tools to detect low-density infections and safeguard elimination gains. Intensified, targeted interventions in identified “malaria hotspots”, including community engagement and vector control, are crucial to eliminate residual foci and prevent disease resurgence.